Obsessive-Compulsive Disorder in PANS/PANDAS in Children: In Search of a Qualified Treatment-A Systematic Review and Metanalysis - Salvatore Cocuzza; Antonino Maniaci; Ignazio La Mantia; Francesco Nocera; Daniela Caruso; Sebastiano Caruso; Giannicola Iannella; Claudio Vicini; Elio Privitera; Jerome Rene Lechien; Piero Pavone (MDPI AG, 2022)
Background: Several treatment options have been proposed for pediatric acute-onset neuropsychiatric syndrome/pediatric autoimmune neuropsychiatric disorder associated with streptococcal infection (PANS/PANDAS). Still, no clear therapeutic protocol has been recognized to prevent these neuropsychiatric diseases. The study aims to report on the literature evidence and different treatment strategies related to these disorders. Methods: We analyzed the last 20 years' English language literature and performed a comprehensive review of the PANS/PANDAS treatment, including studies reporting OCD outcomes post-treatment follow-up. Results: We covered 11 articles in our systematic literature review for a total of 473 patients, of which four studies included 129 surgical subjects and seven papers with 326 medically treated patients. Pooled outcomes analysis, surgical and medical treatment reported an OCD reduction, but no statistical significance was obtained (p < 0.05 for both). Conclusions: Surgical therapy in selected patients can lead to promising results, although further evidence is needed. On the other hand, the role of medical therapy remains controversial, often due to the lack of univocal curative protocols and variable responses depending on the drug used and the timing of administration. Therefore, further investigations are necessary to clarify the most appropriate therapeutic procedure.